LOCAL GOVERNANCE SYNERGIES AND PUBLIC INFRASTRUCTURE: ADVANCING RETAIL REFORM THROUGH INSTITUTIONAL BACKING (Contemporary Journal of Social Science Review, 2025)
This paper discusses the ways in which the Punjab Sahulat Bazaars Authority (PSBA) has used local government partnerships to provide cost-effective, large-scale, and incremental public retail infrastructure in Pakistan. Through its clever use of land supplied by the government formalized in over 100 district-level MoUs, PSBA is able to increase its retail presence without spending precious capital and by integrating operational control, adherence to prices, and regulation of its vendors into municipal and district governments. By creating thousands of direct jobs and tens of thousands of families, the decentralized model creates significant employment and welfare benefits, and providing staple commodities at up to 35% of market prices. The higher financial sustainability, service delivery, and administrative efficiency of PSBA than other similar organizations like PEEF, PAMCO, and LWMC are certified after independent audits. The initiative is an example of polycentric governance and institutional synergy, showing how the empowerment of local actors, common infrastructure and strategic decentralization can improve the delivery of public services. PSBA therefore provides a model that can be seen in other developing economies that ought to be developing legal and citizen-driven institutional reform that would be fiscally disciplined.